2018
DOI: 10.3389/fnhum.2018.00112
|View full text |Cite
|
Sign up to set email alerts
|

Maltreatment, the Oxytocin Receptor Gene, and Conduct Problems Among Male and Female Teenagers

Abstract: The oxytocin receptor gene (OXTR) influences human behavior. The G allele of OXTR rs53576 has been associated with both prosocial and maladaptive behaviors but few studies have taken account of environmental factors. The present study determined whether the association of childhood maltreatment with conduct problems was modified by OXTR rs53576 genotypes. In a general population sample of 1591 teenagers, conduct problems as well as maltreatment were measured by self-report. DNA was extracted from saliva sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 58 publications
3
26
0
Order By: Relevance
“…Interestingly, results regarding anger were nonsignificant. Our findings are aligned with prior research demonstrating the link between maltreatment and conduct disorder and violent tendencies (Andreou, Comasco, Åslund, Nilsson, & Hodgins, ; Docherty, Kubik, Herrera, & Boxer, ). In comparison to nonmaltreated children, maltreated children also show higher levels of behavioral manifestations of negative affect.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, results regarding anger were nonsignificant. Our findings are aligned with prior research demonstrating the link between maltreatment and conduct disorder and violent tendencies (Andreou, Comasco, Åslund, Nilsson, & Hodgins, ; Docherty, Kubik, Herrera, & Boxer, ). In comparison to nonmaltreated children, maltreated children also show higher levels of behavioral manifestations of negative affect.…”
Section: Discussionsupporting
confidence: 91%
“…On the contrary, we aimed to focus on the single stressor of maternal verbal aggressive behavior in early infancy. Our null findings on OXTR variants rs53576 and rs2268498 are in contrast with our hypothesis and the studies [18], but in line with the study of Tollenaar et al [19], in which no interaction was shown of neither rs53576 nor rs2268498 and childhood maltreatment by retrospective recall. Interestingly, ample evidence suggests possible psychological resilience in rs53576 GG carriers, compared to A-allele carriers [44,45], due to their innate higher support seeking, higher levels of optimism, mastery, self-esteem and decreased emotion-focused coping following unsupportive responses, compared to the A-allele carriers.…”
Section: Discussionsupporting
confidence: 87%
“…Of note, evidence of gene-environment interaction of early life stress and rs53576 is contradictory and solely based on retrospective recall. After several kinds of maltreatment in childhood (emotional, physical or sexual abuse; emotional or physical neglect), G-allele carriers have shown increased depressive symptoms [17,18], and conduct problems (in females only) [19] and GG carriers showed a higher risk of emotional dysregulation [20], compared to A-carriers. However, a study on adults with clinically diagnosed depression and anxiety disorders showed no interaction of rs53576 with one or more types of childhood maltreatment [21].…”
Section: Introductionmentioning
confidence: 99%
“…This allele has also been related to prosopagnosia 53 , high levels of physical aggression and hostility 54 and low emotion recognition and resilience skills 55 . G-carriers showed higher levels of retrospective self-report of inhibition and adult separation anxiety 56 and, compared to A-carriers, are more vulnerable to antisocial behavior if they experience maltreatment 57 . This SNP also has interesting anatomical associations: the A allele was associated with larger amygdalar volume in healthy Asian adult 58, 59 , a phenotype typically identified in the early stages of autism 58 , and which correlated with heightened amygdala response during two functional magnetic resonance imaging (fMRI) tasks that involved viewing socially-relevant face stimuli 59 .…”
Section: Resultsmentioning
confidence: 91%